2015
DOI: 10.4103/2278-0513.148915
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the role of human cytomegalovirus in the invasive ductal breast carcinoma

Abstract: Background: Breast cancer is the most common type of female malignancy. Increasing evidence in the last 10 years suggests that human cytomegalovirus (HCMV) is associated with several human malignancies including breast cancer. This study aimed to investigate HCMV in invasive ductal breast carcinoma by enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry (IHC). Materials and Methods: A total of 50 samples of the cancer mass and non-neoplastic safe margin (SM) tissues of breast cancer collected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Previous studies found that HCMV was detected in 7.4% to 100% in breast cancer tissue [45,51,54,57,[59][60][61][62], however, other studies did not detected CMV in breast cancer tissue [42,53,59]. In a recent study we detected HCMV DNA in 20% of breast cancer tissue by using PCR [63], which was lower to that reported by others [64,65] in Iraqi population. While EBV was detected in 26.7% in our recent study [63], however, other studies detected EBV in 6.5% to 35.25% in breast cancer tissue [43,55,60,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80].…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…Previous studies found that HCMV was detected in 7.4% to 100% in breast cancer tissue [45,51,54,57,[59][60][61][62], however, other studies did not detected CMV in breast cancer tissue [42,53,59]. In a recent study we detected HCMV DNA in 20% of breast cancer tissue by using PCR [63], which was lower to that reported by others [64,65] in Iraqi population. While EBV was detected in 26.7% in our recent study [63], however, other studies detected EBV in 6.5% to 35.25% in breast cancer tissue [43,55,60,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80].…”
contrasting
confidence: 68%
“…The association between HCMV and EBV infections and development of breast cancer depend on the detection of viral particle in breast cancer tissue and / or serological studies [36,37,44,[51][52][53][54][55][56][57][58]. Previous studies found that HCMV was detected in 7.4% to 100% in breast cancer tissue [45,51,54,57,[59][60][61][62], however, other studies did not detected CMV in breast cancer tissue [42,53,59]. In a recent study we detected HCMV DNA in 20% of breast cancer tissue by using PCR [63], which was lower to that reported by others [64,65] in Iraqi population.…”
mentioning
confidence: 99%
“…These findings support a relationship between HCMV and carcinogenesis (26).In this study, we investigated the frequency of HCMV in tissue samples of 50 women suffering from breast cancer by using nested-PCR. Several studies indicated that HCMV infection has been linked to the malignant phenotype, particularly with glioblastoma (4).Many studies have indicated a association between HCMV with breast cancer, but they have shown different results (19). Dolores Utrera-Barillas1 and his colleagues were unable to support the hypothesis that HCMV infection might be correlated with tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was revealed that HCMV gene products influence regulation of cell cycle, and inhibit apoptosis; moreover, they activate angiogenesis and metastatic phenotype and, cause the increased rate of mutation, thus overlapping with all the established hallmarks of cancer cells (18). Furthermore, HCMV displays immunosuppressive properties, leading to the tumor cells escape from immune surveillance mechanisms (19). Regardless of the absence of evidence concerning the presence of HCMV in human breast glandular tissues, breast glandular epithelium is considered as a probable reservoir for persistent infection of HCMV in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was revealed that HCMV gene products influence regulation of cell cycle, and inhibit apoptosis; moreover, they activate angiogenesis and metastatic phenotype [10] . Furthermore, HCMV displays immunosuppressive properties, leading to the tumor cells escape from immune surveillance mechanisms [11] . The current study was initiated with the aim of finding out whether EBV and HCMV is associated with breast cancer in Sudanese women.…”
Section: Nacs000560 3(2)2019mentioning
confidence: 99%